ANALISIS DAMPAK PARTISIPASI PEREMPUAN DALAM USAHA SEKTOR INFORMAL TERHADAP PEMBERDAYAAN PEREMPUAN BERDASARKAN KOEFISIEN KONTINGENSI CRAMER - Daru D., Albertus; Irawati, Desrina Yusi (Heuristic, 2017)
This research was conducted to find the changing phenomenon in women informal business actors that impact on women empowerment in Surabaya area by using cross sectional and Cramer’s contingency coefficient. The tools of women empowerment used are decision making in home economics, economic resilience, and mobility. The results of the questionnaires tell us that women had an important role in decision-making in home improvement, household expenses, secondary needs expenditure, bank loans, and children's schools, but the mobility level was still low. The results of cross-sectional analysis and Cramer’s contingency coefficient analysis known that women with relatively equal and or greater income compared to husband, have more role in household economic problem decision making compared to them who have relatively lower income. In addition, the expectancy value of women with economic resilience have lower household mobility. Keywords: female empowerment, informal effort, cross sectional, Cramer’s contingency coefficient